2008
DOI: 10.1093/toxsci/kfn105
|View full text |Cite
|
Sign up to set email alerts
|

Nonclinical Safety, Pharmacokinetics, and Pharmacodynamics of Atacicept

Abstract: Atacicept, a soluble recombinant fusion protein of the human immunoglobulin (Ig) G(1) Fc and the extracellular domain of the human transmembrane activator and calcium modulator and cyclophylin ligand interactor receptor, acts as an antagonist of both B lymphocyte stimulator and a proliferating-inducing ligand. Here we determined the nonclinical safety, pharmacokinetics and pharmacodynamics of atacicept in mice and cynomolgus monkeys. Subcutaneous atacicept treatment (twice weekly in cynomolgus monkeys, three t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 38 publications
5
41
0
Order By: Relevance
“…2A) mice. These data showed a strong correlation with previous studies suggesting that belimumab and TACI-IgG effectively reduce the number of circulating mature B cells but not memory B cells (10,11).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…2A) mice. These data showed a strong correlation with previous studies suggesting that belimumab and TACI-IgG effectively reduce the number of circulating mature B cells but not memory B cells (10,11).…”
Section: Discussionsupporting
confidence: 89%
“…2D) were decreased in lupus-like mice. Previous studies have shown that TACI-IgG does not reduce memory B cells (10,11). However, there is no marker for memory B cells in mice (12).…”
Section: Taci-igg Upregulated Il-15 In Lupus-like and Eae Micementioning
confidence: 96%
See 1 more Smart Citation
“…We and other researchers have shown that similar to belimumab, another BAFF inhibitor, atacicept (TACI-IgG), leads to some degree of B cell depletion, with the effect of atacicept being more rapid than that of belimumab [6,25,32]. To expand upon this, we isolated B cells from TACI-IgG-treated mice with lupus-like disease and used Affymetrix microarrays to detect overall changes in gene expression in these cells.…”
Section: Introductionmentioning
confidence: 99%
“…It reduces circulating mature B-cell and plasma cell levels in the spleen and bone marrow, inhibits T-cell activation [15]. The EAE model on the background of C57BL/6 mice was induced with MOG33-55 in CFA and then treated with TACI-IgG described in Materials and methods.…”
Section: Blockade Of Baff With Taci-igg Reduced Rag1 and Rag2 Expressionmentioning
confidence: 99%